Mezzogiorno feudale Feudi e nobiltà da Carlo di Borbone al Decennio francese - Rao, Anna Maria (Clio. Saggi di scienze storiche, archeologiche e storico-artistiche, 2022)
The volume deals with the theme of the feudal question, crucial for the history of the Mezzogiorno, in a long eighteenth century, from the Austrian period to the beginning of nineteenth century. Historiographic debate, legal treaties, philosophical and economic writings, administrative documents, rules and disputes: around feudalism and the role of the feud in the processes of ennobling and social mobility there is a whole interweaving of government interventions, reflections, protests, sometimes rebellions. The feudal question is confirmed as a problematic node of reform policies, of civil and economic development projects of Sicilies in the context of European transformations, and of the historiographic tradition on and of the South. Not only that but, far from a mere polemical invention of the Enlightenment writers, it re-emerges as a constitutive dimension of the social, political and legal organization, although certainly far from representing southern history as a whole. Attempts at reform and resistance unfold throughout the century, from Charles of Bourbon and his minister Bernardo Tanucci up to the anti-feudal law of 1799 and the subversive laws of Giuseppe Bonaparte and Gioacchino Murat.